Tele-ophthalmology as an effective triaging tool for acute ophthalmic concerns - Townsend, Natalie A.; Shah, Shalini; Reyes, Joshua; Townsend, Justin H.; Bozung, Alison; Ricur, Giselle; Aboumourad, Rami J. (Frontiers in Ophthalmology, 2025)
IntroductionThe purpose of this study is to determine baseline demographics and utilization trend of an on-demand, synchronous tele-ophthalmology triage program in evaluating acute ophthalmic concerns during the COVID-19 Public Health Emergency.MethodsSetting: Single-center retrospective chart review of telemedicine visits conducted by ophthalmologists and optometrists from University of Miami’s Bascom Palmer Eye Institute. Patient population: 6227 patients comprised 7138 telehealth encounters. All patient encounters were included in the retrospective review without exclusions and only the primary diagnoses were categorized from October 1, 2020 to April 30, 2023. Main outcomes measures: Descriptive statistics of the telemedicine model, utilization trends, baseline patient demographics, and primary diagnoses were performed for all virtual eye care encounters during the study period.ResultsUtilization of the synchronous telemedicine platform increased during the study period. The median age of patients was 51 (IQR, 36-65) years. Patients predominantly self-identified as female (63.27%), White (72.7%), and non-Hispanic/Latino (48.2%). General external adnexa (44.1%), conjunctival disorders (15.5%) and ocular surface symptoms (15.4%), made up 75.0% of the visits during the study period. Furthermore, 63.4% of patients were new to Bascom Palmer Eye Institute, 67.1% had never engaged in telemedicine, and 96.5% of encounters were successfully completed through video conferencing.DiscussionDuring the COVID-19 pandemic, there was significant utilization of an on-demand synchronous ocular telemedicine program to address acute concerns. This retrospective chart review demonstrates the utility of telemedicine as an important and effective tool to triage and provide care during the COVID-19 Public Health Emergency.